Comparative Study of impacts of Dapsone Monotherapy and Multidrug Therapy on Occurrence and Detection Rate of New Cases of Leprosy in 7 Provinces of Region 4 - Kamnuantip, Vilai (Journal of Health Science of Thailand, 1994)
The author has conducted a study to compare between the efficacy of mass treatment programme launched by Dapsone Monotherapy from 1983-1987 and multidrug therapy (MDT) from 1988-1992 in 7 provinces covered by Leprosy Center Region 4, Ratchaburi. Ten indicators has been used to measure such impact. The comparative results of epidemiological changes as measured by the ten indicators were presented and discussed. The overall changes in the observed pattern from her finding in 7 provinces of Leprosy Center Regions 4, Ratchaburi revealed and evident more definitely that MDT has more efficacy in lowering both the prevalence (85% by MDT, 40% by Dapsone) and the incidence (as reflected by case-detection rate) (67% by MDT, 25% by Dapsone). The results from some of remaining indicators also support the more rapid decline of leprosy as impact from MDT implementation. All relation factors has also been discussed and suggested that most of these indicators should be of great value to further assess active leprosy transmission in the other zones of low endemicity and under full coverage by MDT.